Marcel Duchamp - Ades, Dawn 1943-; Cox, Neil; Hopkins, David 1955- (Thames & Hudson, 2021)
Genius. Anti-artist. Charlatan. Impostor! Since 1914 Marcel Duchamp has been called all of these. No artist of the 20th century has aroused more passion and controversy, nor exerted a greater influence on art, the very nature of which Duchamp challenged and redefined as concept rather than product by questioning its traditionally privileged optical nature. At the same time, he never ceased to be engaged, openly or secretly, in provocative activities and works that transformed traditional artmaking procedures.00Written with the enthusiastic support of Duchamp's widow, this is one of the most original and important books ever written on this enigmatic artist, and challenges received ideas, misunderstanding and misinformation
First published in the United Kingdom in 1999 as "Marcel Duchamp" by Thames & Hudson Ltd., London. First published in 1999 in paperback in the United States of Amercia as "Marcel Duchamp" by Thames & Hudson Inc., New York. - Revised and expanded edition
Keywords: Duchamp, Marcel -- 1887-1968; Objektkunst; Surrealismus